Literasi Media Digital bagi Gen-Z di MAN 1 Kota Malang: Digital Media Literacy for Gen-Z in Islamic Elementary School 1 Malang City - Anang Sujoko; Desi Dwi Prianti; Dicky Wahyudi; Mutiara Rahmadini Satya Lestari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The behavior of Indonesian netizens is considered the most disrespectful in Southeast Asia, and most netizens in Indonesia are dominated by Gen-Z, who have the highest internet addiction rates. This Community Service Program focuses on digital media literacy for Gen-Z in Malang City. We conducted this program using a participatory method at MAN 1 Malang City with several approaches: a digital media literacy seminar for Gen-Z and an interactive discussion on the use of digital media with Gen-Z. The results of this community service program provide awareness on the use of digital media for Gen-Z students in MAN 1 Malang, regarding: The principles of communication in the use of social media, the Consequences of using digital media on personal data and social interactions, and Production of educational content through digital media. The interactive discussion process shows an imbalance between knowledge and practice of using social media, such as Gen-Z has not yet understood the bad consequences of using social media. However, it has become a user of social media. Another thing, Gen-Z has understood the age limit of social media use, but they are fighting it on the grounds of seeking information and entertainment. Through this community service program, we provide digital literacy model designs to MAN 1 Malang City to demonstrate to Gen-Z students.